A co‐flow structure for goal‐directed internal change. (January 2017) - Gambardella, Pascal J.; Polk, Deborah E.; Lounsbury, David W.; Levine, Ralph L.
Abstract: We describe a co‐flow structure that models internal, goal‐directed changes to an attribute (e.g., employee loyalty) of fundamental material (e.g., employees). This co‐flow accommodates problems not adequately modeled with an existing, generic structure. Our structure builds on the co‐flow proposed by Hines, which uses an information delay to model external change to an attribute. We use a first‐order information delay to model both external changes to the attribute from the material stock and internal changes from an internal goal for the attribute. We provide an exact, dynamic solution for this co‐flow enabling us to precisely describe its equilibrium and non‐equilibrium behavior. Several examples are provided and discussed, including a situation where a management program is designed to increase average employee loyalty. In addition, we review applications of traditional and Hines co‐flow structures to provide background and to describe our evolutionary path towards design of the new co‐flow. Copyright © 2017 System Dynamics Society